Characteristics of PM and PAHs Emitted from Oil-fired Process - Ming Wei Chang; Minh Man Trinh; Chian Kou Lien; Moo Been Chang (Aerosol and Air Quality Research)
Abstract Sampling and analysis of NOx, SO2, filterable particulate matter (FPM), FPM2.5, condensable particulate matter (CPM), and polycyclic aromatic hydrocarbons (PAHs) emitted from an oil-fired boiler equipped with efficiency of electrostatic precipitator (ESP) as air pollution control devices (APCDs) were conducted. Moreover, the emission characteristics of these pollutants were also evaluated at two loadings, i.e., low (30%) and high (80%) capacities. The results show that the NO concentration (90 ppm) emitted from the oil-fired boiler at low loading was lower than that of the high loading (176 ppm) while SO2 concentrations are close under two loading conditions. In terms of particulate matter, the concentrations of FPM, FPM2.5, and CPM measured in the stack at low loading were 0.2, 0.1, and 51.2 mg Nm−3, respectively. As the boiler loading was increased from 30% to 80%, the concentrations of FPM, FPM2.5, and CPM increased to 1.1, 0.6, and 65.0 mg Nm−3, respectively. The total concentrations of PAHs in high loading and low loading oil-fired boilers were 28.3 and 24.4 µg Nm−3, respectively, and the contribution of gas-phase PAHs to the total PAHs was higher than 90%. Regarding the distribution of PAHs species, Nap is the dominant congener of the oil-fired boiler while BcFE is the major contributor for toxic equivalent concentrations. In addition, air pollutant emission factors reported in literatures were compiled and compared those obtained in this study. The results show that the emission factors of PAHs and FPM obtained for this oil-fired boilers are lower than the values measured in other studies.